Оптимальне використання OpenGL та Vulkan - Цапко, Б. В. (ХНУРЕ, 2024)
The purpose of this work is to make the optimal choice between the OpenGL and Vulkan APIs depending on the needs of developers to obtain the required performance characteristics based on the implementation of similar optimization methods in both APIs. The methods of graphic modeling, their implementation and methods of reproduction, various approaches to the optimization of graphic modeling for certain methods of visualization and processing of graphic objects are considered. Techniques such as using shaders, optimizing textures and buffers have been thoroughly reviewed and compared in terms of performance and how they are implemented in the OpenGL and Vulkan APIs.
Keywords: OpenGL; Vulkan; API; graphic